Advancing the management of primary immunodeficiency diseases in Latin America: Latin American Society for Immunodeficiencies (LASID) Initiatives (2012)
ABSTRACT: Primary immunodeficiency diseases (PIDD) are associated with significant morbidity and mortality and result in a significant public health burden. This is in part due to the lack of appropriate diagnosis and treatment of these patients. It is critical that governments become aware of this problem and provide necessary resources to reduce this impact on health care systems. Leading physicians in their respective countries must be supported by their own governments in order to implement tools and provide education and thus improve the diagnosis and treatment of PIDD. The Latin American Society of Primary Immunodeficiencies (LASID) has initiated a large number of activities aimed at achieving these goals, including the establishment of a PIDD registry, development of educational programmes and guidelines, and the introduction of a PIDD fellowship programme. These initiatives are positively impacting the identification and appropriate treatment of patients with PIDD in Latin America. Nevertheless, much remains to be done to ensure that every person with PIDD receives proper therapy.